Stock trading using computational intelligence - Zhu, Ming. (2010)
Computational Intelligence has been widely used in recent years in many areas, such as speech recognition, image analysis, adaptive control and time series prediction. This research attempts to explore the usefulness of neural network and support vector machine in financial market. Two popular stock market indexes have been studied: Hong Kong Hang Seng Stock Index and Dow Jones Transportation Index. The performance of neural network and support vector machine are evaluated in two dimensions: error in forecasting and trading profits.